1976
DOI: 10.1071/ar9760779
|View full text |Cite
|
Sign up to set email alerts
|

Temperature/light interactions and the effect of seed source on germination of annual ryegrass (Lolium rigidum Gaud.) seeds

Abstract: Germination of Lolium rigidum seeds, in the light (12 hr day length) and in the dark, was studied at constant and alternating (12/12 hr) temperatures in the range 8–35°C. Seeds had after-ripened for 22 weeks. Different constant temperature optima for germinability were found: 27° in light and 11° in dark. Germinability at alternating temperatures in darkness was determined solely by the minimum temperature of the alternation, and there was no response to thermoperiodicity per se. In contrast, light and alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…The results indicate that this mediterranean grass species germinates best under cooler conditions and that optimum germination requires low alternating temperatures, which in fact, simulate the environmental conditions prevalent at autumn sowing time in regions of Natal where ryegrass is grown for seed production. Similar results were reported for L. rigidum (Gramshaw, 1976). (Table 1).…”
Section: Resultssupporting
confidence: 79%
“…The results indicate that this mediterranean grass species germinates best under cooler conditions and that optimum germination requires low alternating temperatures, which in fact, simulate the environmental conditions prevalent at autumn sowing time in regions of Natal where ryegrass is grown for seed production. Similar results were reported for L. rigidum (Gramshaw, 1976). (Table 1).…”
Section: Resultssupporting
confidence: 79%
“…Non-indigenous Mediterranean weeds are also shown to prefer cooler conditions for germination; for example, the seeds of Lolium and Avena did not germinate well above 26 and 20°C respectively (Quail and Carter 1968;Gramshaw 1976). The germination rate for the first collected samples was therefore greatest between March and June, ceasing in July (Figure 3), a period that also marks the end of winter season.…”
Section: Seedling Densities and Plant Species Emerging From Dungmentioning
confidence: 93%
“…Cocks & Donald (1973) showed that germinations with diurnal temperature fluctuations greater than 5°C were higher (mean 79% compared with 66%) than those with fluctuations less than 5°C for three temperature ranges: 15-20°C, 20-25°C and 25-30°C. However, Gramshaw (1976) found that in the dark there was close agreement between the percentage germination at any temperature alternation and the germination at a constant temperature equal to the minimum ofthe alternation. In the light, maximum temperature had the dominant eflect.…”
Section: Germination and Dormancymentioning
confidence: 81%
“…Germination at 24712°C in darkness of L. rigidum seed from diflerent field sources varied between 78 and 95%. These differences were not apparent in light where germination ranged from 95 to 100%-LSD 5-3% (Gramshaw, 1976).…”
Section: Germination and Dormancymentioning
confidence: 93%
See 1 more Smart Citation